All Days 2006
DOI: 10.2118/99555-ms
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Integrated Dynamic Surveillance Tool Improves Field-Management Practices

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThis paper describes solutions developed using a dynamic surveillance tool to automate several workflow processes of the reservoir management, production engineering, and R&D Center at Saudi Aramco. The objective is to provide improved efficiency in field management practices, while enhancing collaboration between reservoir and production engineers; ultimately resulting in improved decision-making process.The solutions provided include a combination of smart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The method was originally introduced by Hall and modified by Earlougher to account for the effects of injection duration. It has been implemented for analyzing injection wells with the assumption of a series of steady-state injection conditions [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The method was originally introduced by Hall and modified by Earlougher to account for the effects of injection duration. It has been implemented for analyzing injection wells with the assumption of a series of steady-state injection conditions [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have reported on alternative approaches to achieve this objective; Oberwinker et al (2006) described an IT system that allows engineers to rapidly evaluate and solve potential problems and illustrated the applicability at a US field operated by Murphy E&P; the concept of surveillance systems has also emerged as a valuable application that can provide relevant information to optimize the operation as Al-Fattah et al (2008) reported. These authors stressed the automation of specific workflows where they noted a significant benefit as the surveillance system resulted in improved collaboration between various experts in the organization.…”
Section: Introductionmentioning
confidence: 99%